Upaya Meningkatkan Efektifitas Pembelajaran Fiqih Melalui Metode Diskusi pada Siswa kelas XI di MAS Miftahul Ulum Tlambah Karangpenang Sampang: Efforts to Increase the Effectiveness of Fiqh Learning Through Discussion Methods for XI Grade Students at MAS Miftahul Ulum Tlambah Karangpenang Sampang - Holla, Mat (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The learning process is a system. Thus, achieving process standards to improve the quality of education can start from analyzing each component that can shape and influence the learning process The objectives to be achieved from this study are as follows: To determine the increase in student learning effectiveness in learning Fiqh through discussion methods in class XI students at MAS. Miftahul Ulum Sampang, To determine the student's response to the discussion method in Fiqh learning class XI at MAS. Miftahul Ulum Sampang, To determine the increase in student learning completeness in Fiqh learning for grade XI students at MAS. Miftahul Ulum Sampang. Based on the results of research that has been conducted by researchers obtained that the average achievement results of students in class XI in the pre-cycle stage amounted to 68.60 while the standard Minimum Completeness Criteria (KKM) Fiqh determined by the madrasah is 70. The average value although above the KKM standard determined by the school but still needs to be improved. From the data obtained at the pre-cycle stage, there were 9 students who still did not reach the KKM. The percentage of questionnaire activities and student observations in cycle II obtained an average class score of 77.56%. This increase was also followed by changes in student behavior that were more active, enthusiastic, and focused in the learning process. Thus, it can be concluded that the application of the discussion method in improving learning effectiveness.